2022
DOI: 10.1007/s00204-022-03299-x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of animal testing by integrated approaches to testing and assessment (IATA): a call for in vivitrosi

Abstract: Alternative methods to animal use in toxicology are evolving with new advanced tools and multilevel approaches, to answer from one side to 3Rs requirements, and on the other side offering relevant and valid tests for drugs and chemicals, considering also their combination in test strategies, for a proper risk assessment.While stand-alone methods, have demonstrated to be applicable for some specific toxicological predictions with some limitations, the new strategy for the application of New Approach Methods (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…IATA are science-based approaches that integrate NAMs and mechanistic knowledge for hazard characterization, in a specific regulatory context ( Caloni et al, 2022 ). The AOP framework can be particularly useful in this case to facilitate the identification of the most suitable assays for measurement of MIE or KEs to predict adverse health effects ( Tollefsen et al, 2014 ; Willett, 2019 ), as demonstrated by the examples in the following paragraph.…”
Section: Existing Case Studies Of Aop Application In Chemical Hazard ...mentioning
confidence: 99%
“…IATA are science-based approaches that integrate NAMs and mechanistic knowledge for hazard characterization, in a specific regulatory context ( Caloni et al, 2022 ). The AOP framework can be particularly useful in this case to facilitate the identification of the most suitable assays for measurement of MIE or KEs to predict adverse health effects ( Tollefsen et al, 2014 ; Willett, 2019 ), as demonstrated by the examples in the following paragraph.…”
Section: Existing Case Studies Of Aop Application In Chemical Hazard ...mentioning
confidence: 99%
“…time, skills and experiences, animal housing, special equipment, and consumables, including food), despite its impacts in human health while minimizing the safety and well-being of animals and research practitioners [ 20 ]. In the field of toxicology, many alternatives have been proposed [ 21 ], and implementation of replacement using organoids etc. have been actively proposed even in veterinary research [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The central call of Tox-21c to move to a mechanistic toxicology of perturbed pathways of toxicity implies the use of multiple tests and types of evidence. These integrated testing strategies (ITS), termed integrated approaches to testing and assessment (IATA) by the Organisation for Economic Cooperation and Development (OECD) (Tollefsen et al, 2014), and defined approaches, have been discussed in this series (Hartung et al, 2013a), a workshop (Rovida et al, 2015a), and a more recent review (Caloni et al, 2022). Some progress, especially the defined approaches on skin sensitization 2 , is noted (Kleinstreuer et al, 2018;Kolle et al, 2020).…”
Section: Challenge 1: Testing Strategies Instead Of Individual Testsmentioning
confidence: 99%
“…High-throughput data generation for relevant big data that answers important safety questions, e.g., realistic exposures, potencies, mixtures, interindividual differences. Andersen et al, 2019;Jacobs et al, 2019;de Souza Santos et al, 2018;Aschner et al, 2017;Gordon et al, 2015;Patlewicz et al, 2014;Juberg et al, 2014;Smirnova et al, 2014;Hartung and Corsini, 2013;Parks Saldutti et al, 2013;Rossini and Hartung, 2012;Basketter et al, 2012;Kuegler et al, 2010;Hartung and Hoffmann, 2009;Leist et al, 2008a; Krewski et al, 2022;Maertens et al, 2022;Farhat et al, 2022;Caloni et al, 2022;Hoffmann et al, 2022a,b;Hartung, 2017cHartung, , 2021bHoffmann et al, 2017;Linkov et al, 2015;Hartung, 2009bMetabolomics Lippa et al, 2022Evans et al, 2020;Beger et al, 2019; ALTEX 35, 306-352. doi:10.14573/altex.1712081 Basketter, D. A., Clewell, H., Kimber, I. et al (2012). A roadmap for the development of alternative (non-animal) methods for systemic toxicity testing.…”
Section: Technology-enabled Toxicologymentioning
confidence: 99%